2018
DOI: 10.26334/2183-9077/rapln4ano2018a46
|View full text |Cite
|
Sign up to set email alerts
|

A aquisição das consoantes laterais do português europeu por aprendentes chineses

Abstract: The present study examined the production of European Portuguese (EP) lateral consonants by 14 Chinese learners, through a picture naming task eliciting the target segments in all possible syllable and word-level positions. Our results illustrate that /l/ is stable in singletons (100% target-like) due to the positive transfer from Mandarin Chinese. However, it is very often vocalized in codas (only 16.7% target-like production, [ɫ]), which might be attributed to a phonetically based tendency (Graham, 2017; Joh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
39
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 7 publications
(47 citation statements)
references
References 13 publications
7
39
0
1
Order By: Relevance
“…To return to our first research question, we hypothesized that the previously-reported L2 prosodic effect on the acquisition of EP /l/ and /ɾ/ by L1-Mandarin learners [1,2] could be accounted for by CLI. The results of our delayed imitation task with naïve Mandarin listeners largely replicated the modifications employed by L1-Mandarin learners, as shown in Table 1.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To return to our first research question, we hypothesized that the previously-reported L2 prosodic effect on the acquisition of EP /l/ and /ɾ/ by L1-Mandarin learners [1,2] could be accounted for by CLI. The results of our delayed imitation task with naïve Mandarin listeners largely replicated the modifications employed by L1-Mandarin learners, as shown in Table 1.…”
Section: Discussionmentioning
confidence: 99%
“…Recent research [1,2] has shown that second-language (L2) acquisition of the European Portuguese (EP) lateral /l/ and rhotic /ɾ/ by L1-Mandarin learners is conditioned by prosodic position: learners almost never mispronounce EP /l/ in onset, but in coda frequently vocalize it as [w]. EP /ɾ/ is replaced by the learners with [l] in onset, while in coda they delete the segment, insert a schwa (and thus create an onset), or substitute it either with [l], a coronal stop or the Mandarin rhotic [ɻ].…”
Section: Introductionmentioning
confidence: 99%
“…Lin, 2001;Duanmu, 2005;Lin, 2007), since there is no phonological motivation for an underlying fricative /ʐ/, which would be the only voiced obstruent in the Mandarin phonological inventory and would introduce a novel phonological contrast [± voice] to Mandarin (Duanmu, 2007). 8 The phonetic distinction discussed here is restricted to intervocalic position, because a previous study (Zhou, 2017) demonstrated that L1-Mandarin learners do not confuse the EP lateral and the tap in coda position.…”
Section: Phonetic and Phonological Distinction Between The Alveolar L...mentioning
confidence: 97%
“…Despite many similar observations (e.g. Martins, 2008;Espadinha & Silva, 2009), systematic research on this notorious L2 difficulty is a relatively recent enterprise (Zhou, 2017;Liu, 2018;Cao, 2019;Vale, 2020). These experimental studies have revealed that the complexity of this L2 speech learning process goes beyond what was documented in previous descriptive studies, namely, the confusability between /l/ and /ɾ/ (Batalha, 1995;Martins, 2008), since L1-Mandarin learners' acquisition of this novel phonological contrast seems to be shaped by the interaction between different prosodic positions, speech modalities and representational levels.…”
Section: One Of the Most Perceptible Characteristics In Chinese-accentedmentioning
confidence: 99%
See 1 more Smart Citation